Bidirectional anisotropic palladium nanozymes reprogram macrophages to enhance collaborative chemodynamic therapy of colorectal cancer. (1st October 2022) - Chen, Xu; Jia, Zhi; Wen, Yayu; Huang, Yuqin; Yuan, Xiaoyu; Chen, Yutong; Liu, Yanan; Liu, Jie
Abstract: In the complex tumor microenvironment (TME), tumor-associated macrophages (TAMs) play an important role in immunosuppression and tumor growth; hence, tumor cells are no longer the only target during tumor treatment. However, how to simultaneously target both tumor cells and TAMs to effectively eliminate the tumor remains a challenge. Herein, based on the specific receptors for cancer cells and TAMs, we prepared bidirectional anisotropic palladium nanoclusters (Pd-HA+Pd-M@R NPs) to simultaneously target tumor cells and TAMs for enhancing the therapeutic effect. In these nanoclusters, the Pd-HA part was obtained by modifying hyaluronic acid (HA) on the surface of ultra-small Pd nanozymes that could target CT26 cells. Moreover, with the high peroxidase (POD) and catalase (CAT) activity of Pd nanozymes, Pd-HA NPs directly caused cancer cell death by producing H2 O2 and highly toxic reactive oxygen therapy (ROS) through chemodynamic therapy (CDT). The other part of Pd NPs functioned as a carrier that linked mannose (Man) and the imiquimod molecule (R837) to obtain Pd-M@R NPs, which could specifically connect the mannose receptor of TAMs and perform targeted reprogramming of TAMs to M1 phenotype to reverse immunosuppression and further activate immunotherapy to form "double therapy". Therefore, the strategy of "double therapy" provides new sights for treating malignant tumors. Statement of significance: The bidirectional anisotropic Pd nanoclusters (Pd-HA+Pd-M@R NPs) that can simultaneously target the tumor cells and TAMs with the modification of HA and mannose, respectively. Under the biodirectional anisotropic effect, the Pd nanozymes in Pd-HA can directly kill CT 26 cells through catalyze producing toxic ROS. The Pd-M@R exhibited effectively delivery the imiquimod molecule (R837) to TAMs and specifically induced it transformed into M1 phenotype to reverse tumor immunosuppression to form the "double therapy". Graphical abstract: Image, graphical abstract